Planetary Atmospheric Electricity - Leblanc, François; Aplin, Karen; Yair, Yoav; Harrison, Giles; Lebreton, Jean Pierre; Blanc, M. (Space Sciences Series of ISSI, 2008)
This volume presents our contemporary understanding of atmospheric electricity at Earth and in other solar system atmospheres. It is written by experts in terrestrial atmospheric electricity and planetary scientists. Many of the key issues related to planetary atmospheric electricity are discussed. The physics presented in this book includes ionisation processes in planetary atmospheres, charge generation and separation, and a discussion of electromagnetic signatures of atmospheric discharges. The measurement of thunderstorms and lightning, including its effects and hazards, is highlighted by articles on ground and space based instrumentation, and new missions.Theory and modelling of planetary atmospheric electricity complete this review of the research that is undertaken in this exciting field of space science. This book is an essential research tool for space scientists and geoscientists interested in electrical effects in atmospheres and planetary systems. Graduate students and researchers who are new to the field will benefit from the introductory overviews and can quickly expand their knowledge by studying the subsequent sections.